Export/import procedures and documentation - Johnson, Thomas E., 1948- (AMACOM, 2010)
In the ever-changing world of complex international rules, laws, and regulations, even seasoned export/import professionals may find themselves in unfamiliar situations. This comprehensive answer book supplies readers with a clear view of the entire process, explaining the ins and outs of shipping and insurance; currency exchange; dealing with banks; contracts; customs; and transportation. Completely revised and including 140 sample contracts, documents, and ready-to-use forms--Export/Import Procedures and Documentation contains up-to-the-minute information on new security procedures, the movem.